Predictive value of the neutrophil-to-lymphocyte ratio for treatment response in patients diagnosed with definite or probable autoimmune encephalitis/encephalopathy - Ogami, Shuhei; Koh, Jinsoo; Miyamoto, Katsuichi; Mori, Megumi; Takahashi, Maiko; Nakayama, Yoshiaki; Sakata, Mayumi; Hiwatani, Yasuhiro; Kajimoto, Yoshinori; Ishiguchi, Hiroshi; Ito, Hidefumi (Frontiers in Neurology, 2023)
Introduction: Autoimmune encephalitis/encephalopathy (AE) is a complex and heterogeneous disease, making it difficult to predict the prognosis. The neutrophil-to-lymphocyte ratio (NLR) has emerged as a potential prognostic tool, but its usefulness remains a matter of debate. This study aimed to explore prognostic factors in cases of clinically definite or probable AE, including those with autoantibody-negative, or unknown status. Methods: Data on patients diagnosed with definite or probable AE, including those with autoantibody-negative, or unknown status, were retrospectively collected from the admission records of our department between January 2013 and December 2022. These patients were then categorized into either a good-or poor-response group, based on their shortterm treatment response. Clinical characteristics, auxiliary examinations, and treatments were compared between the two groups. A multivariable logistic regression model was constructed to identify independent predictors of poor short-term treatment response by Akaike information criterion backward stepwise method. Results: A total of 31 patients were included in the final analysis, with 18 of them included in the poor-response group. In the univariable analysis, the poorresponse group had a higher proportion of patients with a modified Rankin Scale (mRS) high score upon admission, female, epileptic seizures, or NLRs of 3.93 or higher than the good-response group (all p < 0.10). Furthermore, the multivariable logistic regression analysis revealed that the mRS score upon admission (OR: 5.51, 95% confidence intervals [CI]: 1.29-23.50, p = 0.02), epileptic seizures (OR: 10.01, 95% CI: 1.16-86.66, p = 0.04), and NLRs of 3.93 or higher (OR: 11.37, 95% CI: 1.12-114.68, p = 0.04) were significantly associated with poor short-term treatment response.The NLR may play a supplementary role in predicting the short-term treatment response in patients 2 This is a provisional file, not the final typeset article diagnosed with definite or probable AE, including those with autoantibody-negative, or unknown status.